Gender Inequalities and Menstrual Health: An Analysis of Access to Products and Practices in Bahía Blanca (Buenos Aires, Argentina) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2026)
This study was conducted by IDEAL Bahía Blanca and the Gender and Sexual Diversity Observatory of the Universidad Nacional del Sur in Bahía Blanca, Buenos Aires, Argentina. Its aim was to gather data on access to menstrual management products (MMPs) and menstrual health practices within the city. A quantitative, exploratory study was carried out through a self-administered, anonymous questionnaire, which yielded 542 responses, the majority of which were from cisgender women.The results indicate that, although two-thirds of respondents had received prior information about menstruation, this knowledge was acquired primarily within the family environment, and to a lesser extent from schools or the healthcare system. More than two-thirds reported interrupting educational, occupational, or recreational activities during menstruation, primarily due to pain or lack of access to MMPs. Eighty per cent of participants considered MMPs to be expensive, and one-third reported experiencing financial difficulties in obtaining them. In some cases, this led to the use of inadequate alternatives that posed risks to their health.These findings underscore the role of menstruation as a factor contributing to gender and social inequality, limiting the exercise of rights related to education, employment, and health. The results highlight the need for comprehensive public policies that ensure equitable access to menstrual products, reliable information, and adequate conditions to support menstrual health.
Keywords: Menstrual management; Menstrual Health; Sexual Health; Gender inequality; Public Policy